2023
DOI: 10.1186/s12987-023-00442-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate carrier 1 is present in retinal microvessels and crucial for the inner blood retinal barrier integrity

Abstract: Background Reduced folate carrier 1 (RFC1; SLC19a1) is the main responsible transporter for the B9 family of vitamins named folates, which are essential for normal tissue growth and development. While folate deficiency resulted in retinal vasculopathy, the expression and the role of RFC1 in blood-retinal barrier (BRB) are not well known. Methods We used whole mount retinas and trypsin digested microvessel samples of adult mice. To knockdown RFC1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“… 74 Recent observations that aspects of early DR may be reversed with the use of a high dose-methylfolate cocktails suggest a practical way to overcome central and retinal folate insufficiency due to deficient intake, methylation impairment, or transport. 23 , 78 This has important implications for RVO ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Recent observations that aspects of early DR may be reversed with the use of a high dose-methylfolate cocktails suggest a practical way to overcome central and retinal folate insufficiency due to deficient intake, methylation impairment, or transport. 23 , 78 This has important implications for RVO ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Ocufolin ® has been shown to lower homocysteine, lower RVP, lower systolic blood pressure, increase conjunctival and retinal perfusion, increase retinal venous blood flow, and increase capillary density in the macula. 32 – 35 , 78 The ingredients of Ocufolin ® ( Table 1 ) have previously been published. 32 Additionally, coupled with anti-VEGF therapy, Ocufolin ® has sufficient B12 to maintain optimal anti-VEGF effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analysis of single-cell RNA expression profiles derived from different human and mouse brain regions using a high-throughput and low-cost single-cell transcriptome sequencing method called EasySci revealed that highly pericyte-enriched expression was notable for SLC6A12 and SLC19A1. The immunohistochemical technique of staining for both antibodies was strongly positive in small blood vessels and was far more effective than a PDGFR-β antibody at staining pericyte-like cells in human brain sections ( Gurler et al, 2023 ; Sziraki et al, 2023 ).…”
Section: Complexities In Pericyte Markersmentioning
confidence: 97%
“…In our recent studies, where we used mice brain sections, whole-mount retinas, and retinal and cerebral microvessel isolates, we demonstrated Slc19a1 (Mus musculus symbol for SLC19A1) protein expression in mice retinal and brain microvessels. 2,3 SLC19A1 expression at the protein level had not previously been studied in the pericytes of the retina and the brain, despite its consistent detection in the transcripts of mural cells. 4 We applied commercial primary antibodies targeted to different regions-MyBioSource (MBS9134642) and Sigma-Aldrich (AV44167)-against SLC19A1 for immunohistochemistry.…”
mentioning
confidence: 99%
“…In line with the findings of Sziraki et al, we showed for the first time that Slc19a1 protein is present in the pericytes and endothelial cells of the retina comprising the inner bloodretina barrier, as well as the cerebral pericytes. 2,3 It is established in pre-clinical studies that pericytes do not have a specific marker, thus presenting certain challenges in studies focusing on their morphology and functions. The available, acceptable, and extensively used markers in literature such as platelet growth factor receptor β (PDGFR-b), NG2 (Cspg4), CD13 (aminopeptidase N), and vimentin are not entirely pericyte-specific and can only reliably identify pericytes when combined with morphological and location-based criteria.…”
mentioning
confidence: 99%